Paranoid personality and frontline employee's proactive work behaviours: a moderated mediation model of empathetic leadership and perceived psychological safety. Issue 1 (2nd December 2020) - Bani-Melhem, Shaker; Mohd. Shamsudin, Faridahwati; Mazen Abukhait, Rawan; Quratulain, Samina
Abstract : Purpose: This study expands on research related to the dark side of personality traits by examining how individual dark personality affects proactive work behaviours. Specifically, the authors consider paranoia as a dark personality trait and propose that it negatively relates to perceived psychological safety and indirectly affects frontline employees' (FLEs) willingness to report customer complaints as well as their extra-role customer service. The authors also posit that empathetic leadership is a focal, contextual factor that mitigates the impact of paranoia on perceived psychological safety and, consequently, the willingness to report customer complaints and engage in extra-role customer service behaviour. Design/methodology/approach: The model was tested on a sample of 252 FLEs using process macro (Hayes, 2017) and AMOS. Data were collected from FLEs working in different hospitality organisations using a time-lagged design; supervisor-rated employee extra-role customer service was also measured. Findings: The authors found that FLEs with a paranoid personality trait had a lesser sense of psychological safety at work, which reduced their willingness to engage in proactive work behaviours. However, this negative effect was mitigated by the presence of an empathetic leader. Originality/value: The results are important because research has yet to determine which actions managers should take to counter the negative effects of dark personalities in the workplace.